ECG Quiz no. 21 - Okreglicki, A. (SA Heart Journal, 2017)
A 47 year-old man with a past medical history of diabetes mellitus and hypertension only, presented with an illness for one week with general body aches, rigors, decreased effort-tolerance, dyspnoea, and no syncope or palpitations. On examination he was ill: febrile, pulse rate 60, BP 100/40, JVP elevated with cannon waves, 2/6 ejection systolic murmur and 2/4 early diastolic murmur along the left sternal margin. The ECG was done on arrival.